2018
DOI: 10.17813/1086-671x-23-4-401
|View full text |Cite
|
Sign up to set email alerts
|

Why We March: The Role of Grievances, Threats, and Movement Organizational Resources in the 2017 Women's Marches

Abstract: We use Metropolitan Statistical Area-level data to investigate the emergence and size of the 2017 Women's Marches. Our findings indicate that the protests can be understood through both grievances and threats felt in the aftermath of Trump's election and movement organizational resources. While the impact of movement resources is as expected (more protest in MSAs with greater resources), the effect of grievances and threats is complex. Cautions concerning the marches in both African American and Hispanic commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 0 publications
1
34
0
Order By: Relevance
“…CCC: News and Twitter: Text Accounts feature the highest correlations and best model fit regardless of the subset of data or operationalization of protest size. Wealthier, more Democratic, and more populous areas generated larger protests, matching others' results (McKane and McCammon 2018).…”
Section: Resultssupporting
confidence: 82%
“…CCC: News and Twitter: Text Accounts feature the highest correlations and best model fit regardless of the subset of data or operationalization of protest size. Wealthier, more Democratic, and more populous areas generated larger protests, matching others' results (McKane and McCammon 2018).…”
Section: Resultssupporting
confidence: 82%
“…The legacy of prior mobilizations included experienced activists, well-developed repertoires of tactics, politicized understandings of particular issues, and organizational infrastructures-as well as alliances, rivalries, and resentments. McKane and McCammon (2018) consider how prior experiences may have discouraged participation in the Resistance. They find that areas with larger percentages of African Americans were less likely to have Women's March protests in 2017, and that areas with larger percentages of Latinx residents tended to have smaller protests.…”
Section: The Emergence Of the Resistance: Continuity And Changementioning
confidence: 99%
“…Andrews, Caren, and Browne (2018) observed that Resistance protests encompassed an unusually wide range of issues, noting over a hundred protests in its first year held for eleven major issues; marches for science, followed by race and immigration, attracted the largest crowds. Some scholars have analyzed these Resistance protests for evidence of the Marchers' goals, for instance, by studying the demographics of areas where protests took place (McKane & McCammon, 2018), or asking protest participants to identify their priority issues (Fisher, 2019;Fisher, Dow, & Ray, 2017 Others, however, question the centrality of specific policy positions to the Resistance. Putnam and Skocpol (2018) report that most Indivisible members they met did not emphasize a progressive political orientation, so much as the 6 of 13 -MARESCA AND MEYER electoral gains that would make a more responsive government possible (Putnam & Skocpol, 2018).…”
Section: What Are We Resisting?mentioning
confidence: 99%
See 1 more Smart Citation
“…By all accounts, the 2017 Women's March mobilized an impressive number of participants. Undoubtedly, part of the reason for this mass mobilization was the activists’ use of digital and social media (McKane and McCammon ). Like many contemporary social movements, the Women's March mobilized through the use of information and communication technologies (ICTs); in fact, it began originally as a Facebook event (Fisher et al.…”
Section: Introductionmentioning
confidence: 99%